2004
DOI: 10.1007/bf03018547
|View full text |Cite
|
Sign up to set email alerts
|

Les concentrations plasmatiques de ropivacaïne sont similaires pendant le bloc continu du plexus lombaire réalisé par voie antérieure trois- en- un et par voie postérieure de la loge du psoas

Abstract: Although the posterior PSOAS block results in higher early plasma concentrations of local anesthetic than the anterior three-in-one FEM block, both techniques are equivalent with regards to their potential toxicity when a continuous infusion is administered. Local anesthetic accumulation occurs with an infusion of ropivacaine 0.2% at 12 mL.hr(-1) and can lead to potentially dangerous concentrations at 48 hr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 14 publications
0
14
1
Order By: Relevance
“…26 mg/h for both catheters. Even though Kaloul et al (2004b) found potentially toxic levels when 24 mg/h was infused, no signs of toxicity were observed in our study. Even 28 mg/h did not cause symptoms in a study by Morin et al (2005).…”
Section: Discussioncontrasting
confidence: 83%
“…26 mg/h for both catheters. Even though Kaloul et al (2004b) found potentially toxic levels when 24 mg/h was infused, no signs of toxicity were observed in our study. Even 28 mg/h did not cause symptoms in a study by Morin et al (2005).…”
Section: Discussioncontrasting
confidence: 83%
“…From the literature available to date, the maintenance of a catheter for longer than 36 hr probably increases the risks for the patient without any clearly demonstrable benefit over iv PCA. 24,25 In conclusion, no differences in analgesia were seen between continuous PSOAS (psoas compartment) blockade and continuous three-in-one FEM blockade for postoperative pain relief in patients undergoing TKR. As the former has been associated with severe complications, the latter may be the regional anesthetic technique of choice in patients undergoing TKR.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, maintenance of a catheter for a duration of 48 hr may increase the risks of infection and, depending on the rate and concentration of the local anesthetic used, may result in local anesthetic toxicity. 24,25 The first question was addressed in a study that compared a control group without regional anesthesia, a group with a single-shot FEM block, and a group with a continuous FEM block. 26 Compared to the control group, a reduction in dynamic VAS pain scores was seen in the groups with FEM blockade only in the recovery room.…”
Section: Discussionmentioning
confidence: 99%
“…Although the safety of continuous infusion is reported, it may lead to the accumulation of the local anesthetic that is administered at large volumes and had a potential risk of toxicity after prolonged periods of infusions [7,8]. There were no clinical symptoms or signs of local anesthetic toxicity during the study period.…”
Section: Discussionmentioning
confidence: 99%